EXPERIENCE OF THE ORGANIZATION OF THE MEDICO-SOCIAL HEALTH CARE DEPARTMENT AT A PEDIATRIC POLYCLINIC - Z. A. Roslova; T. Yu. Man'kova; A. V. Kim; N. V. Ustinova (Вопросы современной педиатрии)
The analysis of functioning of a medico-social health care department at a pediatric polyclinic of St. Petersburg is shown in this article. The data on efficacy of this department are represented. The necessity of its allocation as a separate unit, providing the organization of practical interaction between all of the concerned structures and institutions of social protection of children at difficult living conditions, is proved.